A systematic review of efficacy of Collaborative Assessment and Management of Suicidality (CAMS) in managing suicide risk and deliberate self-harm in adult populations. (December 2019) - Hanratty, Donal; Kilicaslan, Jan; Wilding, Helen; Castle, David
Objective: Evaluate the efficacy of Collaborative Assessment and Management of Suicidality (CAMS) in managing suicide risk and deliberate self-harm in adults. Methods: Ten databases were searched for publications referring to CAMS or the Suicide Status Form. Results were evaluated by two reviewers. Results: Limited evidence that CAMS is effective in reducing suicide risk and deliberate self-harm in adult populations. Conclusions: Although CAMS appears to show promise in managing suicidal patients across a range of measures, further evidence is needed to clarify its efficacy in managing suicide risk and deliberate self-harm.